Deletion of MyD88 in astrocytes prevents β‐amyloid‐induced neuropathology in mice. Issue 2 (22nd October 2022) - Jong Huat, Tee; Onraet, Tessa; Camats‐Perna, Judith; Newcombe, Estella A.; Ngo, Kim C.; Sue, Ashley N.; Mirzaei, Mehdi; LaFerla, Frank M.; Medeiros, Rodrigo
Abstract: As the understanding of immune responses in Alzheimer's disease (AD) is in its early phases, there remains an urgency to identify the cellular and molecular processes driving chronic inflammation. In AD, a subpopulation of astrocytes acquires a neurotoxic phenotype which prompts them to lose typical physiological features. While the underlying molecular mechanisms are still unknown, evidence suggests that myeloid differentiation primary response 88 (MyD88) adaptor protein may play a role in coordinating these cells' immune responses in AD. Herein, we combined studies in human postmortem samples with a conditional genetic knockout mouse model to investigate the link between MyD88 and astrocytes in AD. In silico analyses of bulk and cell‐specific transcriptomic data from human postmortem brains demonstrated an upregulation of MyD88 expression in astrocytes in AD versus non‐AD individuals. Proteomic studies revealed an increase in glial fibrillary acidic protein in multiple brain regions of AD subjects. These studies also showed that although overall MyD88 steady‐state levels were unaffected by AD, this protein was enriched in astrocytes near amyloid plaques and neurofibrillary tangles. Functional studies in mice indicated that the deletion of astrocytic MyD88 protected animals from the acute synaptic toxicity and cognitive impairment caused by the intracerebroventricular administration of β‐amyloid (Aβ). Lastly, unbiased proteomic analysis revealed that loss of astrocytic MyD88 resulted in altered astrocyte reactivity, lower levels of immune‐related proteins, and higher expression of synaptic‐related proteins in response to Aβ. Our studies provide evidence of the pivotal role played by MyD88 in the regulation of astrocytes response to AD. Main Points: MyD88 is upregulated in astrocytes in Alzheimer's disease. Deletion of MyD88 in astrocytes protects against β‐amyloid‐induced synaptic toxicity and cognitive impairment in mice.